LINGKUNGAN SE8AGAI FAKTOR RISIKO TERJADINYA CHIKUNGUNYA STUDI KASUS DI WILAYAH KERJA PUSKESMAS KANDANGSAPI KOTA PASURUAN TAHUN 2014 - Syauban Amaldi Susomo; A T. Diana Nerawati; Sudjarwo . (GEMA LINGKUNGAN KESEHATAN, 2014)
Chikungunya is an environment-based disease; an infectious disease caused by the Chikungunya virus(CHIKV), transmitted by Aedes aegypti and Aedes a/bopictus. The disease is characterized by fever, jointpain, muscle pain, rash and seizures or loss of consciousness.Environmental factors are is closely linked tothe occurence of Chikungunya and particularly the presence of Chikungunya virus and the vector. On theother hand, social environmental factors also contribute to the physical environmental condition of thehost. The purpose of the present study was the determine to what extent the environmental factorscontributed to the occurence of Chikungunya in the service area of Kandangsapi Community HealthCenter.The present study was of analytical nature using a retrospective approach in which the effects(disease or health status) were identified at this :time and then the risk factors were identified for theirprecence in the past. Subjects of this study were 14 patients living in Kelurahan Petamanan, located withinthe service area of Kandangsapi Community Health Center. They were diagnosed with Chikungunya inMay-January2014. Data were analyzed by using odds ratios.Result showed that poor social environment contributed to the occurence of Chikungunya (OR)3,2 times higher than that of good social environment, whereas the physical did not pose any risk to theoccurence of Chikungunya (OR=l)It is recomended that Kandangspi Community Health Center provides elaborate information onChikungunya, 3M measures and healthy homes principles to the communities with regard to theprevention and control of Chikungunya